Simulation of light-induced degradation of μc-Si in a-Si/μc-Si tandem solar cells by the diode equivalent circuit. (January 2016) - Weicht, J A; Hamelmann, F U; Behrens, G
Abstract: Silicon-based thin film tandem solar cells consist of one amorphous (a-Si) and one microcrystalline (μc-Si) silicon solar cell. The Staebler - Wronski effect describes the light- induced degradation and temperature-dependent healing of defects of silicon-based solar thin film cells. The solar cell degradation depends strongly on operation temperature. Until now, only the light-induced degradation (LID) of the amorphous layer was examined in a-Si/μc-Si solar cells. The LID is also observed in pc-Si single function solar cells. In our work we show the influence of the light-induced degradation of the μc-Si layer on the diode equivalent circuit. The current-voltage-curves (I-V-curves) for the initial state of a-Si/pc-Si modules are measured. Afterwards the cells are degraded under controlled conditions at constant temperature and constant irradiation. At fixed times the modules are measured at standard test conditions (STC) (AM1.5, 25°C cell temperature, 1000 W/m 2 ) for controlling the status of LID. After the degradation the modules are annealed at dark conditions for several hours at 120°C. After the annealing the dangling bonds in the amorphous layer are healed, while the degradation of the pc-Si is still present, because the healing of defects in pc-Si solar cells needs longer time or higher temperatures. The solar cells are measured again at STC. With this laboratory measured I-V-curves we are able to separate the values of the diode model: series Rs and parallel resistance Rp, saturation current Is and diode factor n.